Internship at Southreef Properties Ltd - Narang, Somil; Dhanuka, Suyash (2007)
The management project was undertaken on behalf of Southreef Properties Ltd, a mixed use, mixed tenure development. Southreef Properties is developing a mixed tenure development in the city centre of Nottingham.